Printable and flexible graphene pH sensors utilising thin film melanin for physiological applications - Tehrani, Z.; Whelan, S. P.; Mostert, A. B.; Paulin, J. V. [UNESP]; Ali, M. M.; Ahmadi, E Daghigh; Graeff, C. F.O. [UNESP]; Guy, O. J.; Gethin, D. T. (My University, 2020)
The application of highly sensitive pH sensors manufactured in volume at low cost has great commercial interest due to an extensive array of potential applications. Such areas include industrial processing, biotechnology and medical diagnostics particularly in the development of point of care (POC) devices. A novel printable electrochemical pH sensor based on graphene and pigment melanin (PGM), was designed and produced by using a screen printing process that enables up scaling for potential commercial application. We demonstrate a highly sensitive pH sensor (62 mV pH-1 ± 7) over a pH range from 5 to 8, with high stability and superior performance when compared with a number of existing devices and making it suitable for physiological applications.
Keywords: blood plasma; grapheme; low cost manufacturing; melanin; pH Sensor; screen print